Interpretation on coexistence or association of thrombocytopenia with malaria (Journal of Pathology of Nepal, 2019)
Background: Malaria is a major health problem especially in developing countries. It is a major causeof morbidity and mortality especially in the tropics. There are several hematological changes in thisparticular disease, which includes thrombocytopenia, anemia , atypical lymphocytosis and infrequentlyintravascular coagulation. The aim of the study is to detect and compare the severity of varioushematological changes, especially thrombocytopenia in the particular type of malaria.Materials and Methods: This was an observational study done on the patients attending the outpatientand inpatient departments clinically suspected for malaria in Nobel Medical College, Biratnagar, Nepal.Thick and thin slides were made and stained with Leishman’s stain for malarial parasites and also antigentests were included wherever necessary. Other tests included were, complete blood counts.Results: Amongst the included 800 patients with suspicion of malaria, 135 (17%) patients demonstratedmalarial parasites on peripheral blood film. Male predominance in male to female predominance of 3.5:1was observed. Total number of 120 out of 135 had thrombocytopenia. Thrombocytopenia was observedhigher in P. Vivax (79.3%) followed by Mixed infection (17%) and P. falciparum (3.7%) respectively.Conclusion: Anemia with mainly thrombocytopenia was mainly seen in P. Vivax type followed by P.Falciparum. Since thrombocytopenia is associated with malaria, which is demonstrated in our study,treating physicians should keep malaria as one of the differential diagnosis in patients with fever and lowplatelets.